Surgical dental treatment in patients with Von Willebrand Syndrome: Literature review (Research, Society and Development, 2024)
Von Willebrand syndrome occurs due to a genetic defect that prevents or minimizes blood clotting. Therefore, people with this condition are more susceptible to episodes of bleeding. Therefore, the number of patients with some blood pathology is significant, confirming the importance of the nature of this work. The general objective of this study is to point out how Von Willebrand syndrome impacts the performance of oral surgical procedures, in addition to explaining its repercussions on the blood clotting cascade. This literature review was carried out using the Virtual Health Library (BVS), Pubmed/Medline, and Google Scholar databases, within the time frame of the last 20 years (2004-2024), where studies in Portuguese and English were selected. Therefore, oral surgeries pose a risk to this group of patients; however, there are measures that can be addressed that will ensure a safe surgical procedure.